Arbitrage breakdown in WTI crude oil futures: An analysis of the events on April 20, 2020. (June 2022) - Burns, Christopher B.; Kane, Stephen
Abstract: This study provides novel analysis of the events in the WTI crude oil futures market on April 20, 2020. We detail how the arbitrage linkages between the NYMEX CL contract and the e-mini NYMEX QM contract broke down and report new information about the unusual market conditions on that date. After establishing that most price discovery happens in the more liquid CL contract, we show how these two contracts decoupled in the May 2020 spot period. Next, using supervisory CFTC data, we document that the typical arbitragers did not participate in the WTI crude oil markets on April 20. This change in the composition of arbitragers had important implications for the unusual settlement prices in the CL contract. Third, we use generalizable non-parametric methods to rank the values observed in terms of price deviations, realized volatility and spreads to similar crude oils. We find the May 2020 spot month to have the largest values of these measures across all spot periods from 2011 to 2020. Finally, we show that natural gas futures markets did not experience a similar price decoupling, suggesting the lack of storage capacity at Cushing played an important role in the WTI crude negative price event. Highlights: On April 20, 2020, the May 2020 NYMEX WTI contract (CL) settled to a negative price. On the same date, prices for the CL and E-mini (QM) contracts decoupled. Distribution of arbitrageurs was significantly different in May 2020 spot period. Supply constraints at Cushing, OK contributed to price anomalies and volatility. Nonparametric methods are used for the analysis.